2020
DOI: 10.17159/2078-516x/2020/v32i1a8622
|View full text |Cite
|
Sign up to set email alerts
|

South African professional Super Rugby players’ lived experiences of career-related traumatic injuries: A descriptive phenomenological analysis

Abstract: Background: Historically, non-career-ending traumatic rugby injury (TRI) has been viewed from a predominantly biological perspective. However, dimensional perspectives, such as the biopsychosocial model, have highlighted the need to incorporate psychosocial understandings of TRI into treatment plans. Aim: To describe the lived experiences of a cohort of traumatically injured South African Super Rugby players in order to add to the body of literature on the subject of TRI exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 17 publications
(62 reference statements)
1
10
0
Order By: Relevance
“…Hall [ 3 ] , drawing from the biopsychosocial model of sports injury rehabilitation processes, [ 10 ] suggested that SRI affects the individual professional rugby player across biological, psychological and social dimensions of their life-world. The biopsychosocial model of sports injury rehabilitation considers seven dimensional influences: injury characteristics, socio-demographic factors, biological factors, psychological factors, social and contextual factors, intermediate biopsychosocial outcomes, and sports injury rehabilitation outcomes.…”
Section: A Multidimensional Approach To Sri Recoverymentioning
confidence: 99%
See 4 more Smart Citations
“…Hall [ 3 ] , drawing from the biopsychosocial model of sports injury rehabilitation processes, [ 10 ] suggested that SRI affects the individual professional rugby player across biological, psychological and social dimensions of their life-world. The biopsychosocial model of sports injury rehabilitation considers seven dimensional influences: injury characteristics, socio-demographic factors, biological factors, psychological factors, social and contextual factors, intermediate biopsychosocial outcomes, and sports injury rehabilitation outcomes.…”
Section: A Multidimensional Approach To Sri Recoverymentioning
confidence: 99%
“…[ 11 ] Players live and work within a somewhat closed system that is potentially sceptical of outsiders, such as psychotherapists. A documented lack of psychotherapeutic referral networks, time and financial constraints, [ 6 ] and a paucity of psychoeducation around psychosocial expectations of injury recovery, [ 1 , 3 , 6 ] ongoing negative stigma associated with acknowledging the onset of CMD and seeking out psychotherapeutic assistance [ 1 , 6 ] seem to precipitate professional rugby players’ reliance on insider (e.g. teammates and medical professionals) support structures during SRI recovery rather than the seeking out or acceptance of external assistance, such as psychotherapists.…”
Section: Socio-cultural Factorsmentioning
confidence: 99%
See 3 more Smart Citations